Epistemological aspects of the economic control - Galassi, Giuseppe (De Computis, Revista Española de Historia de la Contabilidad., 2019)
Epistemology is essential for probing the fundamental issues of the management sciences, included the ‘economic control process’. The paper aims to highlight the connections between economia aziendale, the typical Italian research program, as well as the traditional research programs of Continental European Countries, with a theoretical reconstruction founded also on modern epistemological issues. One fundamental question, for instance, is about the ‘true’ information or knowledge conveyed by a financial statement, taking into account that economia aziendale, the general system, was conceived as consisting of interrelated sub-systems of management, organization and data gathering for planning and control. The ‘economic control’, both antecedent, concomitant and subsequent, refers to the azienda, the economic entity, that is to every kind of economic unit, not only to the business enterprise.The ‘economic control’ is concerned with social responsibility, ethical conduct, as well as with ‘evidence’, ‘proof’, opinions and judgments. The credibility of a hypothesis depends on the associated evidence, so it is not independent from the strength of the entire argument, ‘evidence plus hypothesis’. The ‘degree of confidence’ implies probability, specifically the bayesian approach for modifying early prior valuations in the light of further information, obtaining revised posterior probabilities. The essential requirement of a proof is that it is ‘psychologically satisfying’; the problem of the controller’s independence stresses the controlling ethical standards. The code of ethics and rules of conduct should serve to identify responsibilities and aims involved – greater accountability through better information about ends and means – and to underline the need for a theoretical foundation about ethics of accounting and economic controlling. Of particular interest is the dichotomy ‘subjective-objective’ related also to economic reality, every kind of reality, included physical as well as cultural ones. This brings directly in the field of accounting and ‘entity economics’ metaphors. The economic controlling process is tightly connected to interpersonal analogy and to the ‘social agreement approach’ to ‘objectivity’ and scientific methodology. There is often no possible control through ‘correspondence’ with definite aspects of reality, economic-financial events themselves. System theorists employ many concepts that correspond to ‘independent reality’ only through ‘indicator hypotheses’ such as ‘business income’ magnitude, the best proxy of the economic efficiency of the ‘business entity’.